Method for preparing efficient photocatalyst for photocatalytic degradation of tetracycline by using electric furnace dust

By using ZnFe2O4@ZnO photocatalyst prepared by electric furnace dust, efficient degradation of tetracycline in water is achieved, and the problems of low efficiency and high cost of tetracycline removal in the prior art are solved. The material has the characteristics of magnetic recyclability and has good application prospects.

CN119735261APending Publication Date: 2025-04-01YUNNAN MINZU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411938594.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

As a broad-spectrum antibacterial agent, tetracycline is difficult to metabolize by human and animal organisms, causing it to accumulate in water, posing a serious threat to ecosystems and public health. The prior art has problems of low efficiency and high cost in removing and degrading tetracycline in water bodies.

Method used

The efficient heterojunction photocatalyst ZnFe2O4@ZnO is prepared by using electric furnace dust, and the tetracycline is degraded by photocatalyzing. The method includes collecting electric furnace dust and washing it with ultrasonic water, mixing it with acid and alkali solution for modification, and heat treatment at high temperatures, and finally preparing a ZnFe2O4@ZnO photocatalyst with excellent photocatalytic activity.

Benefits of technology

It has achieved efficient removal of tetracycline in water, has good photogenerated electrons and hole separation capabilities, is simple to operate, is cheap to cost, and the prepared material is magnetically recyclable, solving the problem that photocatalysts are difficult to recycle and reuse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735261A_ABST
    Figure CN119735261A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solid waste recycling and water pollution control and utilization, and particularly relates to a method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline by using electric furnace dust, which comprises the following specific steps: step 1, collecting electric furnace dust from steel plants or other industrial processes; the method comprises the following steps: mixing electric furnace dust with deionized water, carrying out ultrasonic washing, removing surface impurities and soluble salts, filtering, pouring into a drying oven, drying, controlling the temperature of the drying oven at 80-100 DEG C, and continuously drying for 3-10 hours to obtain a solid product; according to the invention, solid wastes generated in the iron and steel industry can be utilized with high added value, and the problems of resource waste, environmental pollution and the like are reduced; the material obtained by roasting has good photo-induced electron and hole separation capability, so that the material has excellent photocatalytic activity and has good application prospects in the field of environmental purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste resource utilization and water pollution control and utilization, and specifically to a method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline by utilizing electric furnace dust. Background Art

[0002] With the acceleration of industrialization and the continuous development of human activities, a large number of organic pollutants are discharged into water bodies, seriously threatening the ecological balance and human health. The discharge of new pollutants has become an important challenge facing global environmental protection. Pharmaceuticals and personal care products (PPCPs) have become a new class of pollutants that pose a serious threat to human health. Antibiotics are one of the main ingredients of pharmaceuticals and personal care products. The industrial processes involved in the production of antibiotics may cause these compounds to be released into water bodies through wastewater discharge. The concentration of antibiotics in surface water, wastewater and drinking water has far exceeded the standard.

[0003] Tetracycline, an antibiotic, is a well-known broad-spectrum antibacterial agent widely used to treat bacterial infections in humans and animals. However, due to the abuse of antibiotics and the high chemical stability of the drug itself, tetracycline is difficult to be metabolized by humans and animals and discharged into water bodies. TC molecules are widely accumulated in aquatic environments, causing serious impacts on ecosystems and public health. In order to solve this problem, various technologies have been developed to remove and degrade TC in water bodies, such as biodegradation, physical adsorption, and advanced oxidation processes (AOPs). As a type of AOPs, photocatalytic treatment technology is a new green process route. It is considered to be a promising strategy for treating TC wastewater because of its advantages such as high efficiency, sustainability, stability, and low cost.

[0004] As a byproduct of the steel industry, electric furnace dust is a solid waste that can burden the environment if not properly handled. Currently, most electric furnace dust is disposed of through landfills, which can have a great impact on the environment. Therefore, converting EAFD into something useful is considered an important way to solve these problems. Recent studies have found that electric furnace dust has unique physical and chemical properties, making it a potential efficient photocatalyst for photocatalytic degradation of organic pollutants in water. Electric furnace dust mainly contains iron and zinc, with iron mainly existing in the form of magnetite (Fe3O4) and zinc ferrite (ZnFe2O4), and zinc existing in the form of zinc ore (ZnO) and zinc ferrite (ZnFe2O4). Among them, ZnFe2O4 and ZnO are common photocatalytic materials used for wastewater purification. Heterojunction photocatalytic materials have been shown to exhibit excellent photocatalytic activity under visible light irradiation. Currently, a large number of studies have focused on the synthesis of such photocatalytic materials using chemical synthesis methods, and the photocatalytic activity of such materials is often affected by their band gap energy, so they are rarely used as photocatalysts in a single phase. In addition, the photocatalysts synthesized by various methods have the problems of high preparation cost and complicated process. Using low-cost solid waste material EAFD to prepare heterojunction photocatalytic materials for wastewater treatment has great application prospects in order to achieve the purpose of treating waste with waste.

[0005] Therefore, a method of using electric furnace dust to prepare a high-efficiency photocatalyst for photocatalytic degradation of tetracycline is proposed to solve the above-mentioned problems. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline using electric furnace dust, so as to solve the problems raised in the above background technology.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline using electric furnace dust, and the specific steps of the method are as follows:

[0008] Step 1: Collect electric furnace dust from steel mills or other industrial processes, mix the electric furnace dust with deionized water, perform ultrasonic washing to remove surface impurities and soluble salts, filter, pour into an oven to dry, control the oven temperature to 80-100°C, and continue drying for 3-10 hours to obtain a solid product;

[0009] Step 2: Mix the electric furnace dust obtained in step 1 with the acid solution, stir for 1-2 hours to remove some metal oxides and other impurities on the surface, then wash with deionized water until neutral, and dry;

[0010] Step 3: Mix the electric furnace dust treated in step 2 with an alkaline solution, stir for 1.5-2 hours to further modify the surface structure, then wash with deionized water until neutral, and dry;

[0011] Step 4: heat-treating the modified electric furnace dust at high temperature, pouring the electric furnace dust into a tube furnace, introducing O2 as a carrier gas, heating to 400-900°C at a heating rate of 10°C / min and maintaining for two hours, and then cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain a photocatalyst;

[0012] Step 5: Add the obtained ZnFe2O4@ZnO photocatalyst to a tetracycline solution with a concentration of 30 mg / L. The dosage of ZnFe2O4@ZnO is 0.1 g / L. After stirring in the dark for 30 minutes to reach adsorption equilibrium, irradiate with a 300W rare element lamp as a simulated light source and start degradation. Within a time interval of 1-2 hours, take out the same volume of reaction solution, filter it through a 0.22μm microporous filter membrane, and then put it into a 2mL HPLC injection vial to observe its color and concentration changes.

[0013] Preferably, in step 1, the solid-liquid ratio of the mixture of electric furnace dust and deionized water is 1:80 g / mL.

[0014] Preferably, when the degradation effect of tetracycline is detected in the later stage, the tetracycline concentration (C t ), the initial concentration of tetracycline was recorded as C0, C t / C0 represents the ratio of the remaining amount of tetracycline after degradation.

[0015] Preferably, the rare element lamp in step five includes a xenon lamp and a mercury lamp.

[0016] Preferably, in step 2, the acid solution selected is dilute sulfuric acid or nitric acid.

[0017] Preferably, in step three, the alkaline solution selected is sodium hydroxide solution.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1) The present invention can utilize the solid waste generated by the steel industry with high added value, reducing problems such as resource waste and environmental pollution;

[0020] 2) The calcined material has good separation ability of photogenerated electrons and holes, thus has excellent photocatalytic activity and has good application prospects in the field of environmental purification. Photocatalysts act as photocatalytic materials in the treatment of antibiotic wastewater, which can effectively remove tetracycline in wastewater. It has the advantages of simple operation, low cost, high removal rate, etc., and can meet the actual application needs;

[0021] 3) The prepared material has the characteristics of magnetic recyclability, which solves the problem of difficulty in recycling and reusing photocatalysts and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the X-ray diffraction diagram of the phase composition of electric furnace dust before and after water washing;

[0023] Figure 2 X-ray diffraction patterns of electric furnace dust at different calcination temperatures;

[0024] Figure 3 This is the performance diagram of tetracycline degradation by electric furnace dust;

[0025] Figure 4 This is a comparison chart of the tetracycline degradation performance of electric furnace dust at different calcination temperatures;

[0026] Figure 5 This is a diagram showing the effect of photocatalyst magnetic separation after the reaction is completed. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In the description of the present invention, it is necessary to understand that the terms "upper", "lower", "front", "back", "left", "right", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0029] See also Figure 1-5 , the present invention provides a technical solution:

[0030] A method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline using electric furnace dust, the specific steps of the method are as follows:

[0031] Step 1: Collect electric furnace dust from steel mills or other industrial processes, mix the electric furnace dust with deionized water, perform ultrasonic washing to remove surface impurities and soluble salts, filter, pour into an oven to dry, control the oven temperature to 80-100°C, and continue drying for 3-10 hours to obtain a solid product;

[0032] Step 2: Mix the electric furnace dust obtained in step 1 with an acid solution, the acid solution is dilute sulfuric acid or nitric acid, stir for 1-2 hours to remove some metal oxides and other impurities on the surface, then wash with deionized water until neutral, and dry;

[0033] Step 3: Mix the electric furnace dust treated in step 2 with an alkaline solution, wherein the alkaline solution is a sodium hydroxide solution, stir for 1.5-2 hours to further modify the surface structure, then wash with deionized water until neutral, and dry;

[0034] Step 4: heat-treating the modified electric furnace dust at high temperature, pouring the electric furnace dust into a tube furnace, introducing O2 as a carrier gas, heating to 400-900°C at a heating rate of 10°C / min and maintaining for two hours, and then cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain a photocatalyst;

[0035] Step 5: Add the obtained ZnFe2O4@ZnO photocatalyst to a tetracycline solution with a concentration of 30 mg / L. The dosage of ZnFe2O4@ZnO is 0.1 g / L. After stirring in the dark for 30 minutes to reach adsorption equilibrium, irradiate with a 300W rare element lamp as a simulated light source and start degradation. Rare element lamps include xenon lamps and mercury lamps. At time intervals of 1-2 hours, take out the same volume of reaction solution, filter it through a 0.22μm microporous filter membrane, and then put it into a 2mL high-performance liquid chromatography injection vial to observe its color and concentration changes.

[0036] In the step 1, the solid-liquid ratio of the mixture of electric furnace dust and deionized water is 1:80 g / mL.

[0037] When tetracycline was tested for degradation in the later stage, high performance liquid chromatography was used to measure the concentration of tetracycline (C t ), the initial concentration of tetracycline was recorded as C0, C t / C0 represents the ratio of the remaining amount of tetracycline after degradation.

[0038] Embodiment 1:

[0039] The specific steps of this method are as follows:

[0040] Step 1: Collect electric furnace dust from steel mills or other industrial processes, mix the electric furnace dust with deionized water, perform ultrasonic washing to remove surface impurities and soluble salts, filter, pour into an oven to dry, control the oven temperature to 80°C, and continue drying for 3 hours to obtain a solid product;

[0041] Step 2: Mix the electric furnace dust obtained in step 1 with the acid solution, stir for 1 hour to remove some metal oxides and other impurities on the surface, then wash with deionized water until neutral, and dry;

[0042] Step 3: Mix the electric furnace dust treated in step 2 with an alkaline solution, stir for 1.5-2 hours to further modify the surface structure, then wash with deionized water until neutral, and dry;

[0043] Step 4: heat-treating the modified electric furnace dust at high temperature, pouring the electric furnace dust into a tube furnace, introducing O2 as a carrier gas, heating to 400°C at a heating rate of 10°C / min and maintaining for two hours, and then cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain a photocatalyst;

[0044] Step 5: Add the obtained ZnFe2O4@ZnO photocatalyst to a tetracycline solution with a concentration of 30 mg / L. The dosage of ZnFe2O4@ZnO is 0.1 g / L. After stirring in the dark for 30 minutes to reach adsorption equilibrium, irradiate with a 300W rare element lamp as a simulated light source and start degradation. Within a time interval of 1 hour, take out the same volume of reaction solution, filter it through a 0.22μm microporous filter membrane, and put it into a 2mL high-performance liquid chromatography injection vial to observe its color and concentration changes;

[0045] Embodiment 2:

[0046] The specific steps of this method are as follows:

[0047] Step 1: Collect electric furnace dust from steel mills or other industrial processes, mix the electric furnace dust with deionized water, perform ultrasonic washing to remove surface impurities and soluble salts, filter, pour into an oven to dry, control the oven temperature to 90°C, and continue drying for 6.5 hours to obtain a solid product;

[0048] Step 2: Mix the electric furnace dust obtained in step 1 with the acid solution, stir for 1.5 hours to remove some metal oxides and other impurities on the surface, then wash with deionized water until neutral, and dry;

[0049] Step 3: Mix the electric furnace dust treated in step 2 with an alkaline solution, stir for 1.75 hours to further modify the surface structure, then wash with deionized water until neutral, and dry;

[0050] Step 4: heat-treating the modified electric furnace dust at high temperature, pouring the electric furnace dust into a tube furnace, introducing O2 as a carrier gas, heating to 800°C at a heating rate of 10°C / min and maintaining for two hours, and then cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain a photocatalyst;

[0051] Step 5: Add the obtained ZnFe2O4@ZnO photocatalyst to a tetracycline solution with a concentration of 30 mg / L. The dosage of ZnFe2O4@ZnO is 0.1 g / L. After stirring in the dark for 30 minutes to reach adsorption equilibrium, irradiate with a 300W rare element lamp as a simulated light source and start degradation. Within a time interval of 1.5 hours, take out the same volume of reaction solution, filter it through a 0.22μm microporous filter membrane, and put it into a 2mL high-performance liquid chromatography injection vial to observe its color and concentration changes;

[0052] Embodiment three:

[0053] The specific steps of this method are as follows:

[0054] Step 1: Collect electric furnace dust from steel mills or other industrial processes, mix the electric furnace dust with deionized water, perform ultrasonic washing to remove surface impurities and soluble salts, filter, pour into an oven to dry, control the oven temperature to 100°C, and continue drying for 10 hours to obtain a solid product;

[0055] Step 2: Mix the electric furnace dust obtained in step 1 with the acid solution, stir for 2 hours to remove some metal oxides and other impurities on the surface, then wash with deionized water until neutral, and dry;

[0056] Step 3: Mix the electric furnace dust treated in step 2 with an alkaline solution, stir for 2 hours to further modify the surface structure, then wash with deionized water until neutral, and dry;

[0057] Step 4: heat-treating the modified electric furnace dust at high temperature, pouring the electric furnace dust into a tube furnace, introducing O2 as a carrier gas, heating to 900°C at a heating rate of 10°C / min and maintaining for two hours, and then cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain a photocatalyst;

[0058] Step 5: Add the obtained ZnFe2O4@ZnO photocatalyst to a tetracycline solution with a concentration of 30 mg / L. The dosage of ZnFe2O4@ZnO is 0.1 g / L. After stirring in the dark for 30 minutes to reach adsorption equilibrium, irradiate with a 300W rare element lamp as a simulated light source and start degradation. Within a time interval of 2 hours, take out the same volume of reaction solution, filter it through a 0.22μm microporous filter membrane, and then put it into a 2mL HPLC injection vial to observe its color and concentration changes.

[0059] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description. Therefore, it is intended to include all changes within the meaning and scope of the equivalent elements of the claims in the present invention, and any figure marks in the claims should not be regarded as limiting the claims involved.

[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline using electric furnace dust, characterized in that: The specific steps of this method are as follows: Step 1: Collect electric furnace dust from steel mills or other industrial processes, mix the electric furnace dust with deionized water, perform ultrasonic washing to remove surface impurities and soluble salts, filter, pour into an oven to dry, control the oven temperature to 80-100°C, and continue drying for 3-10 hours to obtain a solid product; Step 2: Mix the electric furnace dust obtained in step 1 with the acid solution, stir for 1-2 hours to remove some metal oxides and other impurities on the surface, then wash with deionized water until neutral, and dry; Step 3: Mix the electric furnace dust treated in step 2 with an alkaline solution, stir for 1.5-2 hours to further modify the surface structure, then wash with deionized water until neutral, and dry; Step 4: heat-treating the modified electric furnace dust at high temperature, pouring the electric furnace dust into a tube furnace, introducing O2 as a carrier gas, heating to 400-900°C at a heating rate of 10°C / min and maintaining for two hours, and then cooling the temperature to room temperature at a cooling rate of 10°C / min to obtain a photocatalyst; Step 5: Add the obtained ZnFe2O4@ZnO photocatalyst to a tetracycline solution with a concentration of 30 mg / L. The dosage of ZnFe2O4@ZnO is 0.1 g / L. After stirring in the dark for 30 minutes to reach adsorption equilibrium, irradiate with a 300W rare element lamp as a simulated light source and start degradation. Within a time interval of 1-2 hours, take out the same volume of reaction solution, filter it through a 0.22μm microporous filter membrane, and then put it into a 2mL HPLC injection vial to observe its color and concentration changes.

2. The method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline using electric furnace dust according to claim 1, characterized in that: In the step 1, the solid-liquid ratio of the mixture of electric furnace dust and deionized water is 1:80 g / mL.

3. The method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline using electric furnace dust according to claim 1, characterized in that: When tetracycline was tested for degradation in the later stage, high performance liquid chromatography was used to measure the concentration of tetracycline (C t ), the initial concentration of tetracycline was recorded as C0, C t / C0 represents the ratio of the remaining amount of tetracycline after degradation.

4. The method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline using electric furnace dust according to claim 1, characterized in that: The rare element lamps in step 5 include xenon lamps and mercury lamps.

5. The method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline using electric furnace dust according to claim 1, characterized in that: In the step 2, the acid solution selected is dilute sulfuric acid or nitric acid.

6. The method for preparing a high-efficiency photocatalyst for photocatalytic degradation of tetracycline using electric furnace dust according to claim 1, characterized in that: In the step 3, the alkaline solution selected is sodium hydroxide solution.

Citation Information

Patent Citations

  • Preparation method and application of oxygen vacancy-containing zinc oxide / zinc ferrite photocatalyst

    CN113828320A

  • Method for manufacturing photo catalysis using electric arc furnace dust and photo catalysis manufactured with this

    KR1020100129640A